Immunemodulatory Effects of 5-Azacitidin Through Expansion of Functional Regulatory T Cells on Paraneoplastic Inflammation Associated With Myelodysplastic Syndromes: A Case Report - Serizawa, Kentaro; Tanaka, Hirokazu; Morita, Yasuyoshi; Taniguchi, Takahide; Ashida, Takashi; Matsumura, Itaru (Frontiers in Oncology, 2018)
Myelodysplastic syndrome (MDS) is a heterogeneous group of clonal disorders of hematopoietic stem cells, characterized by dysplastic hematopoiesis and dysregulated immune system resulting in various clinical conditions. Paraneoplastic inflammatory syndromes, which are well known to be associated with MDS, show response to immune-modulated therapy and often disappear during the course of hematologic management. Azacitidine (5-Aza) was shown to prolong survival of high-risk MDS patients, however, the effects of 5-Aza on paraneoplastic inflammation in MDS have yet to be elucidated. 5-Aza was administered to a 60-year-old man with MDS accompanying Sweet’s syndrome at a dose of 75 mg/m2/daily subcutaneously for 7 days every 28 days. 5-Aza was not only effective in controlling systemic symptoms caused by paraneoplastic inflammation, but hematologic improvements were also observed after four cycles of the 5-Aza treatment. Immune profiling in peripheral blood before and after 5-Aza treatment revealed that the effector and naive regulatory T cells in lymphocytes drastically increased after the 5-Aza treatment, i.e., 5-Aza might induce a shift in lymphocytic populations toward immunosuppression in this patient. Our results raised the immune-mediated effect of 5-Aza on both dysplastic hematopoiesis and paraneoplastic inflammation in myelodyplastic syndromes.